Pengaruh ESOP Terhadap Kesejahteraan Investor dengan Perubahan Return On Investment (ROI) Sebagai Variabel Intervening - Umi Murtini (Jurnal Riset Manajemen dan Bisnis, 2010)
ESOP is an alternative attempt of companies to reduce any agency cofficts and to increase their bwestors' welfare. This research is aimed at finding the influence of the ESOP on the investors' welfare throagh the improvement of the ROI as the interttening voiable. The investors' welfore is seen from the price fluetuation af the shares (return on shores). This study indicates that the ESOP has a direct and an indirect influence on the price fluctuation of the shares (as the indicators of the irruerstors' weWe). The indirect influerce of the ESOP on the pricefluctuation of the shares is throughthe ROI, sa it is evident that the ROI as the interventingvariable of the ESOP influences the changes of the price of the shmes.Keywordt: ESOP, ROI, the price of share, irwestors'welfme